2006
DOI: 10.1038/nphys427
|View full text |Cite
|
Sign up to set email alerts
|

Tunable refraction and reflection of self-confined light beams

Abstract: Here we report the robust propagation, refraction and reflection of optical spatial solitons at the interface between two regions of a nematic liquid crystal. The ability to independently tune the optical properties of each region enables us to steer the beams by refraction and total internal reflection by as much as −18 and +22 degrees, respectively. Moreover, the extended (nonlocal) and anisotropic response of our system supports polarization healing of the solitons across the interface as well as non-specul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
159
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(170 citation statements)
references
References 25 publications
7
159
2
2
Order By: Relevance
“…The control of their trajectories is relevant in reconfigurable interconnects [1][2][3][4]. In nematic liquid crystals, recent progress on spatial solitons ("Nematicons") and their control include electro-optic and opto-optical deviation and interactions, with overall changes in angle as large as 40 degrees [4][5][6][7][8].…”
mentioning
confidence: 99%
“…The control of their trajectories is relevant in reconfigurable interconnects [1][2][3][4]. In nematic liquid crystals, recent progress on spatial solitons ("Nematicons") and their control include electro-optic and opto-optical deviation and interactions, with overall changes in angle as large as 40 degrees [4][5][6][7][8].…”
mentioning
confidence: 99%
“…Classically, the physics of a beam of light being reflected at an interface is governed by geometric optics law, where the photons are treated as classical particles. In contrast, when considering the wave nature of photons, spatial shifts at the interface appear as longitudinal shift in the incident plane [1][2][3] , or transverse shift normal to the incident plane [4][5][6][7][8][9] , which are known as the Goos-Hänchen (GH) effect and the ImbertFedorov (IF) effect, respectively. Due to all particles possessing the wave-particle duality, the spatial shifts are also expected for other particles.…”
mentioning
confidence: 99%
“…In conclusion, we have demonstrated that judicious doping of nematic liquid crystals and interact to implement simple as well as complex circuits for signal interconnects and processing, including, e.g., bends, [13,15,22] junctions, [23] multiplexers. [14] …”
mentioning
confidence: 99%
“…Hence, nematicon waveguides only exist as long as the defining beam propagates in the medium (or shortly thereafter until material relaxation has completed). They exhibit a fully flexible transverse (graded index) profile and longitudinal shape (trajectory), which can be modified through external stimuli such as electric fields, [13,15,21] as well as through the interaction with other beams, [22,23] offering a wide range of possibilities for realizing three-dimensional circuits and interconnects such as inplane and skew bends, spirals, junctions and splitters. [5] Hence, it would be extremely beneficial or even strategic to acquire the ability to "freeze" such real-time structures into permanent ones crafted in the medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation